6x ( 4x-9y )

Product of monomial and binomial worksheets, solved worksheet problems or exercises with step-by-step work, formative assessment as online test, calculator and more learning resources to learn, practice, assess and master the basic math skills of algebra.

Product of Monomial and Binomial

Name
Grade
School

Date
Questions20
Score

1

Find the product

6x ( 4x-9y )

6x ( 4x-9y )

2

Find the product

3x ( 3x+4y )

3x ( 3x+4y )

3

Find the product

4y ( 4y+3x )

4y ( 4y+3x )

4

Find the product

5x ( 9x+2y )

5x ( 9x+2y )

5

Find the product

5m ( 4m+6n )

5m ( 4m+6n )

6

Find the product

6s ( s+6t )

6s ( s+6t )

7

Find the product

10y ( 2y+x )

10y ( 2y+x )

8

Find the product

-4y ( 6x+y )

-4y ( 6x+y )

9

Find the product

9a ( 6a+6b )

9a ( 6a+6b )

10

Find the product

-2x ( 5x+3y )

-2x ( 5x+3y )

11

Find the product

2s ( 5s-2t )

2s ( 5s-2t )

12

Find the product

12y ( 12y+13z )

12y ( 12y+13z )

13

Find the product

2x ( 9y-2z )

2x ( 9y-2z )

14

Find the product

9a ( 6a+6b )

9a ( 6a+6b )

15

Find the product

-2x ( 5x+y )

-2x ( 5x+y )

16

Find the product

3x ( 4x+5y )

3x ( 4x+5y )

17

Find the product

3x ( 13x+14y )

3x ( 13x+14y )

18

Find the product

-4y ( -4y+3x )

-4y ( -4y+3x )

19

Find the product

x ( 19x+12y )

x ( 19x+12y )

20

Find the product

15m ( 14m-16n )

15m ( 14m-16n )

Solved Worksheet Problems

Show All Workout

1

Find the product

6x ( 4x-9y )

24x6x ( 4x-9y )

Solution

= (6x) x (4x-9y)

= (6x) x (4x) - (6x) x (9y)

= 24x^{2}-54xy

= (6x) x (4x) - (6x) x (9y)

= 24x

2

Find the product

3x ( 3x+4y )

3x3x ( 3x+4y )

Solution

= (3x ) x (3x+4y)

= (3x ) x (3x) + (3x ) x (4y)

= 3x^{2}+4xy

= (3x ) x (3x) + (3x ) x (4y)

= 3x

3

Find the product

4y ( 4y+3x )

16y4y ( 4y+3x )

Solution

= (4y) x (4y+3x)

= (4y) x (4y) + (4y) x (3x)

= 16y^{2}+12yx

= (4y) x (4y) + (4y) x (3x)

= 16y

4

Find the product

5x ( 9x+2y )

45x5x ( 9x+2y )

Solution

= (5x) x (9x+2y)

= (5x) x (9x) + (5x) x (2y)

= 45x^{2}+10xy

= (5x) x (9x) + (5x) x (2y)

= 45x

5

Find the product

5m ( 4m+6n )

20m5m ( 4m+6n )

Solution

= (5m) x (4m+6n)

= (5m) x (4m) + (5m) x (6n)

= 20m^{2}+30mn

= (5m) x (4m) + (5m) x (6n)

= 20m

6

Find the product

6s ( s+6t )

6s6s ( s+6t )

Solution

= (6s) x (s+6t)

= (6s) x (s) + (6s) x (6t)

= 6s^{2}+36st

= (6s) x (s) + (6s) x (6t)

= 6s

7

Find the product

10y ( 2y+x )

20y10y ( 2y+x )

Solution

= (10y) x (2y+x)

= (10y) x (2y) + (10y) x (x)

= 20y^{2}+10yx

= (10y) x (2y) + (10y) x (x)

= 20y

8

Find the product

-4y ( 6x+y )

-24yx-4y-4y ( 6x+y )

Solution

= (-4y) x (6x+y)

= (-4y) x (6x) + (-4y) x (y)

= -24yx-4y^{2}

= (-4y) x (6x) + (-4y) x (y)

= -24yx-4y

9

Find the product

9a ( 6a+6b )

54a9a ( 6a+6b )

Solution

= (9a) x (6a+6b)

= (9a) x (6a) + (9a) x (6b)

= 54a^{2}+54ab

= (9a) x (6a) + (9a) x (6b)

= 54a

10

Find the product

-2x ( 5x+3y )

-10x-2x ( 5x+3y )

Solution

= (-2x) x (5x+3y)

= (-2x) x (5x) + (-2x) x (3y)

= -10x^{2}-6xy

= (-2x) x (5x) + (-2x) x (3y)

= -10x

11

Find the product

2s ( 5s-2t )

10s2s ( 5s-2t )

Solution

= (2s) x (5s-2t)

= (2s) x (5s) - (2s) x (2t)

= 10s^{2}-4st

= (2s) x (5s) - (2s) x (2t)

= 10s

12

Find the product

12y ( 12y+13z )

144y12y ( 12y+13z )

Solution

= (12y) x (12y+13z)

= (12y) x (12y) + (12y) x (13z)

= 144y^{2}+156yz

= (12y) x (12y) + (12y) x (13z)

= 144y

13

Find the product

2x ( 9y-2z )

18xy-4xz2x ( 9y-2z )

Solution

= (2x) x (9y-2z)

= (2x) x (9y) - (2x) x (2z)

= 18xy-4xz

= (2x) x (9y) - (2x) x (2z)

= 18xy-4xz

14

Find the product

9a ( 6a+6b )

54a9a ( 6a+6b )

Solution

= (9a) x (6a+6b)

= (9a) x (6a) + (9a) x (6b)

= 54a^{2}+54ab

= (9a) x (6a) + (9a) x (6b)

= 54a

15

Find the product

-2x ( 5x+y )

-10x-2x ( 5x+y )

Solution

= (-2x) x (5x+y)

= (-2x) x (5x) + (-2x) x (y)

= -10x^{2}-2xy

= (-2x) x (5x) + (-2x) x (y)

= -10x

16

Find the product

3x ( 4x+5y )

12x3x ( 4x+5y )

Solution

= (3x) x (4x+5y)

= (3x) x (4x) + (3x) x (5y)

= 12x^{2}+15xy

= (3x) x (4x) + (3x) x (5y)

= 12x

17

Find the product

3x ( 13x+14y )

13x3x ( 13x+14y )

Solution

= (3x ) x (13x+14y)

= (3x ) x (13x) + (3x ) x (14y)

= 13x^{2}+14xy

= (3x ) x (13x) + (3x ) x (14y)

= 13x

18

Find the product

-4y ( -4y+3x )

16y-4y ( -4y+3x )

Solution

= (-4y) x (-4y+3x)

= (-4y) x (-4y) + (-4y) x (3x)

= 16y^{2}-12yx

= (-4y) x (-4y) + (-4y) x (3x)

= 16y

19

Find the product

x ( 19x+12y )

19xx ( 19x+12y )

Solution

= (x) x (19x+12y)

= (x) x (19x) + (x) x (12y)

= 19x^{2}+12xy

= (x) x (19x) + (x) x (12y)

= 19x

20

Find the product

15m ( 14m-16n )

210m15m ( 14m-16n )

Solution

= (15m) x (14m-16n)

= (15m) x (14m) - (15m) x (16n)

= 210m^{2}-240mn

= (15m) x (14m) - (15m) x (16n)

= 210m

Online Test

Start my Challenge

Find the product 5n(9n-9m)

Find the product 10y(x+8y)

Find the product 7y(x-z)

Find the product 8y(x+z)

Find the product 7q(9q+7p)

Find the product 3n(m+s)

Find the product 4y(x-10y)

Find the product 3n(m+s)

Find the product 6b(a-c)

Find the product 2b(a-6b)

MATH LEARNING RESOURCES AND TOOLS FOR PERSONALIZED LEARNING